2018
DOI: 10.1007/s11010-018-3346-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased accumulation of doxorubicin due to emodin on efflux transporter and LRP1 expression in lung adenocarcinoma and colorectal carcinoma cells

Abstract: Treatment with doxorubicin (dox) and emodin, separately and together, under normoxic and hypoxia-like conditions induced by CoCl, led to greater intracellular compound accumulation over 10 h post-addition in the presence of CoCl in lung adenocarcinoma (A549) and colorectal carcinoma (HCT-15) cell lines. Confocal microscopy revealed that emodin, by itself, showed high cytosolic distribution in both cell lines, at 40 min post-addition but had entered the nuclei by 2 h, while dox entered the nuclei by 40 min. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that emodin and cisplatin alone or in combination can significantly decrease the expression of Pgp and MRP1 in bladder cancer cells (32,35,39). Furthermore, emodin and doxorubicin significantly decrease the expression of Pgp and MRP1 in colon cancer cells (39). In the present study, the effect of emodin on the expression of Pgp and MRP1 in A549 and H460 cells was investigated.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies have demonstrated that emodin and cisplatin alone or in combination can significantly decrease the expression of Pgp and MRP1 in bladder cancer cells (32,35,39). Furthermore, emodin and doxorubicin significantly decrease the expression of Pgp and MRP1 in colon cancer cells (39). In the present study, the effect of emodin on the expression of Pgp and MRP1 in A549 and H460 cells was investigated.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, the drug protein pump mediated by Pgp, MRP and other drug resistance-related proteins, such as BCRP and LRP1, is the main mechanism by which tumors develop MDR (27). Previous studies have demonstrated that emodin and cisplatin alone or in combination can significantly decrease the expression of Pgp and MRP1 in bladder cancer cells (32,35,39). Furthermore, emodin and doxorubicin significantly decrease the expression of Pgp and MRP1 in colon cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of LRP1 protein may be associated with a higher endocytosis of upregulated transporter proteins at the cell surface, which is likely the cause of increased doxorubicin and emodin (an anti-inflammatory agent) accumulation and growth inhibition in lung adenocarcinoma and colorectal carcinoma cells [62]. Additionally, emodin was shown to upregulate LRP1 in a prostate cancer cell as well as nonprostate cell lines A549 (lung), HCT-15 (colon) and MG-63 (bone) under normoxic and hypoxia-like conditions via reactive oxygen species (ROS) generation [63].…”
Section: Low Density Lipoprotein Receptor-related Proteins (Lrps)mentioning
confidence: 99%
“…Additionally, emodin was shown to upregulate LRP1 in a prostate cancer cell as well as nonprostate cell lines A549 (lung), HCT-15 (colon) and MG-63 (bone) under normoxic and hypoxia-like conditions via reactive oxygen species (ROS) generation [63]. Therefore, LRP1 expression may be a point for interventions to promote efficacy of anticancer drugs by allowing their more efficient uptake in lung adenocarcinoma and colorectal carcinoma [62,63].…”
Section: Low Density Lipoprotein Receptor-related Proteins (Lrps)mentioning
confidence: 99%
“…In addition to the direct role of emodin in the treatment of lung cancer, it can also play a good indirect role in the treatment of lung cancer. Emodin has been found to have a significant synergistic effect when used in combination with some drugs for lung cancer that do not work well because of new drug resistance [35] [36].…”
Section: Lung Cancermentioning
confidence: 99%